2014
DOI: 10.1002/jts.21942
|View full text |Cite
|
Sign up to set email alerts
|

Reported Barriers to Mental Health Care in Three Samples of U.S. Army National Guard Soldiers at Three Time Points

Abstract: The military community and its partners have made vigorous efforts to address treatment barriers and increase appropriate mental health services use among returning National Guard soldiers. We assessed whether there were differences in reports of treatment barriers in 3 categories (stigma, logistics, or negative beliefs about treatment) in sequential cross-sectional samples of U.S. soldiers from a Midwestern Army National Guard Organization who were returning from overseas deployments. Data were collected duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 36 publications
(61 reference statements)
2
38
0
Order By: Relevance
“…Critically, outcomes of the present study are comparable to those observed in studies and settings employing more traditional treatment models (e.g., weekly or biweekly sessions), which suggests that CPT retains its efficacy even when administered intensively during very brief periods of time. If replicated, these findings may point to an alternative treatment delivery model that could increase treatment accessibility for many military personnel and veterans with PTSD, a population with relatively low rates of mental healthcare utilization (Hoge et al., ; Maguen, Madden, Cohen, Bertenthal, & Seal, ; Valenstein et al., ). The 2‐week intensive program was associated with higher treatment completion rates and lower dropout rates as compared with reported rates in many clinical trials and naturalistic studies for trauma‐focused therapy (see Imel, Laska, Jakcupcak, & Simpson, , for review).…”
Section: Discussionmentioning
confidence: 92%
“…Critically, outcomes of the present study are comparable to those observed in studies and settings employing more traditional treatment models (e.g., weekly or biweekly sessions), which suggests that CPT retains its efficacy even when administered intensively during very brief periods of time. If replicated, these findings may point to an alternative treatment delivery model that could increase treatment accessibility for many military personnel and veterans with PTSD, a population with relatively low rates of mental healthcare utilization (Hoge et al., ; Maguen, Madden, Cohen, Bertenthal, & Seal, ; Valenstein et al., ). The 2‐week intensive program was associated with higher treatment completion rates and lower dropout rates as compared with reported rates in many clinical trials and naturalistic studies for trauma‐focused therapy (see Imel, Laska, Jakcupcak, & Simpson, , for review).…”
Section: Discussionmentioning
confidence: 92%
“…Prior analysis demonstrated that the prevalence of mental health concerns 12 months postdeployment did not change for serial panel cohorts 45–90 days postdeployment, with 15.8 and 19.0 percent having PTSD and depression symptoms, respectively (Valenstein et al. ). Looking over time at changes in outcomes within individuals who are engaged in VA and non‐VA care is an important next step.…”
Section: Discussionmentioning
confidence: 99%
“…; Valenstein et al. ). Prior research has also found that those with PTSD have high levels of comorbid major depressive disorder and alcohol‐use disorder (Erbes et al.…”
Section: Mental Health Needmentioning
confidence: 98%
“…Data were collected under an approved waiver of written informed consent. For further details of the study, please see [83,84].…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Mental health service utilization in the past year was assessed from 14 items that asked participants to indicate if they ''had received mental health services for a stress, emotional, alcohol, or family problem'' from either general medical or mental health providers in several different settings, including military, civilian, Veterans Affairs health clinics, or Vet Centers (see [83]). An affirmative response to receiving treatment from any of these providers in the past year was used to create a dichotomous variable reflecting any mental health treatment.…”
Section: Mental Health Service Utilizationmentioning
confidence: 99%